Marketing RH: La Marque Emoployeur/ un Levier pour se Demarquer - Idrissi Khadija; Hanaty Chorine; Senihji Khadija (European Scientific Journal, ESJ, 2019)
Today, in a world dominated by digital technology, it is obvious that companies have to integrate new methods of getting work done. This digitalization has changed the work of managers and have made them realized that their methodology has become obsolete. At any rate, the HR function indeed was impacted by this wave of digitization that has overwhelmed all other functions of the company including marketing. Driven by digital technology, the HR function has moved from a support function to a business partner function. This switch marked the advent of the "E-marketing HR", an unexpected marriage that upset the situation. Since then, HR marketing is a renewed approach of HRM, which seeks, on the one hand, to improve the internal attractiveness of the company. On the other hand, it helps to develop the external attractiveness of the company. Thus, this paper focuses on the external attractiveness of the company. To attract candidates, the company needs to focus on improving their brand by communicating its culture. The relationship between the digital employer brand and e-recruitment will therefore be the subject of our article. Our thinking is built on four stages: First we will consider the genesis of HR marketing and its role in the development of the employer brand. The second part will be devoted to the use of web 2.0 in the construction of a digital employer brand and itsimpact on e-recruitment. Finally, we will present some digital recruitment strategies of some multinationals.Aujourd’hui dans un monde dominé par le digital, c’est tout naturel que les entreprises aient intégré des nouveaux modes de travail façonnés par le numeriqué.Cette mutation digitale a modifié le travail des gestionnaires et les a amenés à repenser une méthodologie devenue obsoleté. Et tout état de cause, La fonction RH ne s’échappe pas à cette vague de digitalisation qui a submergé toutes les autres fonctions de l’entreprise y compris le marketing. Emportée par le digital, la fonction RH est passée d’une fonction support à une fonction de partenaire stratégique. Ce passage a marqué l’avènement du «E-marketing RH », un mariage inattendu qui a bouleversé la donne. Dès lors, Le marketing RH est une approche rénovée de la GRH, qui cherche d’une part à améliorer l’attractivité interne de l’entreprise et d’autre part développer son attractivité externe. Nous nous intéressons dans cet article à l’attractivité externe de l’entreprise. En effet pour attirer les candidats l’entreprise est appelée à polir sa marque employeur en véhiculant sa culture. La relation entre la marque employeur et l’e-recrutement sera donc le sujet de notre article. Notre réflexion est construite en quatre étapes : nous verrons en premiers temps la genèse du marketing RH et son rôle dans le développement de la marque employeur. Secundo nous mettons en surbrillance l’usage du web 2.0 dans la construction de la marque employeur numérique et son impact sur l’erecrutement. In fine, nous présentons quelques stratégies de recrutement digital de certaines Multinationales.